EXPLORING GENETIC VARIATION AND IDENTIFICATION OF DIVERGENT ZINC RICH DONORS IN A CORE RICE GERMPLASM - SWAPAN K. TRIPATHY,; URAJ K. BEHERA,; DEBENDRA N. BASTIA,; SAMBIT PATRA,; DIGBIJAYA SWAIN, (The Bioscan, 2019)
An experiment was carried out to explore high Zn donors and to study the extent of genetic divergence based on grain Zn content and agro-morphological traits including seed yield in a set of 47 core germplasm lines of rice. Grain zinc content ranged from 9.2-28.1ppm. The top Zn dense (≥24 ppm) genotypes identified were Nagina 22(28.1ppm), BG 102(25.8ppm), Dudh Kandar (25.6ppm), R-RHZ-7 (24.7ppm) and IR 85850-AC157-1(24.0ppm). Among these, two breeding lines IR 85850-AC157-1(24.0ppm) and R-RHZ-7(24.7ppm) retained high grain zinc content along with moderately high seed yield potential. The set of genotypes were grouped into seven distinct clusters. The elite high Zn local land races “Nagina 22” and “Dudh Kandar” had poor yield potential but showed high genetic divergence. These may serve as valuable material for Zn biofortification breeding.